2021
DOI: 10.1039/d0md00272k
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in synthetic and medicinal chemistry of phosphotyrosine and phosphonate-based phosphotyrosine analogues

Abstract: This review summarizes advances over the last decade in the design of phosphotyrosine and its phosphonate-based derivatives, focusing on their synthesis and medicinal chemistry applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 93 publications
(181 reference statements)
0
22
0
1
Order By: Relevance
“…Therefore, to evaluate whether the Tyr residue affects the binding of ICAM-1 to SRC, we created a phosphomimetic mutant in which the Tyr residue was either unphosphorylated or remains active without the need to be phosphorylated (Fig. 3E ) [ 26 ]. Co-IP and PLA results revealed that when the Tyr residue was substituted with alanine, it did not bind to SRC, whereas when it was substituted with aspartic acid, the binding significantly increased (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to evaluate whether the Tyr residue affects the binding of ICAM-1 to SRC, we created a phosphomimetic mutant in which the Tyr residue was either unphosphorylated or remains active without the need to be phosphorylated (Fig. 3E ) [ 26 ]. Co-IP and PLA results revealed that when the Tyr residue was substituted with alanine, it did not bind to SRC, whereas when it was substituted with aspartic acid, the binding significantly increased (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For a profound understanding of protein tyrosine phosphorylation chemical tools are required to bind, inhibit or manipulate phosphotyrosine binding sites without being prone to enzymatic cleavage or dephosphorylation. To date the most potent “gold standard” phosphotyrosine mimetic is 4‐phosphono‐difluoromethyl‐phenylalanine (PDFM‐Phe) 1 and numerous studies have demonstrated highly potent and selective inhibitors with this structure integrated in peptide sequences (Scheme 1A) [5, 6] . Phosphonic acids, however, are strong acids and form highly polar di‐anions resulting in low membrane permeability and thus inactivity in cells [7]…”
Section: Methodsmentioning
confidence: 99%
“…To date the most potent "gold standard" phosphotyrosine mimetic is 4-phosphono-difluoromethyl-phenylalanine (PDFM-Phe) 1 and numerous studies have demonstrated highly potent and selective inhibitors with this structure integrated in peptide sequences (Scheme 1A). [5,6] Phosphonic acids, however, are strong acids and form highly polar di-anions resulting in low membrane permeability and thus inactivity in cells. [7] Considering that phosphate binding sites are coated with a positively charged surface resulting from cationic arginine residues and from H-bond donors, [8] we hypothesized that fragments containing fluorine atoms with negative partial charge might act as H-bond acceptors and thus might be useful as phosphate mimetics.…”
mentioning
confidence: 99%
“…Für ein fundiertes Verständnis der Proteintyrosin‐Phosphorylierung sind daher chemische Werkzeuge von Nöten, die an die Proteintyrosin‐Bindungstasche binden und diese inhibieren oder manipulieren, ohne dabei enzymatisch gespalten oder dephosphoryliert zu werden. Der derzeitige “Goldstandard” für Mimetika ist 4‐Phosphono‐Difluormethylphenylalanin (PDFM‐Phe) 1 und zahlreiche Studien zeigten hochpotente und selektive Inhibitoren, in denen dieser Baustein in eine Peptidstruktur eingebaut wurde (Schema 1A) [5, 6] . Phosphonsäuren sind jedoch starke Säuren und liegen als hochpolare Dianionen vor, was geringe Membranpermeabilität und daher Inaktivität in Zellen zur Folge hat [7]…”
Section: Methodsunclassified